Injection drug users trained by overdose prevention programs: Responses to witnessed overdoses - Lankenau, Stephen E. (2013)
In response to the growing public health problem of drug overdose, community-based organizations have initiated overdose prevention programs (OPP), which distribute naloxone, an opioid antagonist, and teach overdose response techniques. Injection drug users (IDUs) have been targeted for this intervention due to their high risk for drug overdose. Limited research attention has focused on factors that may inhibit or prevent IDUs who have been trained by OPPs to undertake recommended response techniques when responding to a drug overdose. IDUs (n=30) trained by two OPPs in Los Angeles were interviewed in 2010–11 about responses to their most recently witnessed drug overdose using an instrument containing both open and closed-ended questions. Among the 30 witnessed overdose events, the victim recovered in 29 cases while the outcome was unknown in one case. Participants responded to overdoses using a variety of techniques taught by OPP. Injecting the victim with naloxone was the most common recommended response while other recommended responses included stimulating the victim with knuckles, calling 911, and giving rescue breathing. Barriers preventing participants from employing recommended response techniques in certain circumstances included prior successes using folk remedies to revive a victim, concerns over attracting police to the scene, and issues surrounding access to or use of naloxone. Practical solutions, such as developing booster sessions to augment OPP, are encouraged to increase the likelihood that trained participants respond to a drug overdose with the full range of recommended techniques.